1989
DOI: 10.1002/mrm.1910110205
|View full text |Cite
|
Sign up to set email alerts
|

The effect of gadolinium DTPA on tissue water compartments in slow‐ and fast‐twitch rabbit muscles

Abstract: Proton T2 relaxation and its biexponential components have been determined in rabbit skeletal muscle in the presence and absence of GdDTPA. The effect of GdDTPA, which distributes only in the extracellular space, was greatest in the longer-relaxing T2 component (T22). A 27% reduction in T22 was measured for slow-twitch (red) muscle and 17% for fast-twitch (white) muscle, consistent with the larger extracellular space of the former. Magnetic resonance images demonstrated apparent contrast between red and white … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 31 publications
1
37
0
Order By: Relevance
“…Adzamli et al first reported prolongation of proton T2 and T1 relaxation times in slow-, compared to fast-twitch rabbit muscles, a difference that was proportional to the greater extracellular water content of the slow-twitch fibers. 33 The importance of water compartmentation was substantiated by a higher concentration of infused gadolinium DTPA, a marker of the extracellular space, in slow-twitch fibers. Interestingly, data from one group studying humans reported opposite findings.…”
Section: Muscle Fiber Typingmentioning
confidence: 99%
“…Adzamli et al first reported prolongation of proton T2 and T1 relaxation times in slow-, compared to fast-twitch rabbit muscles, a difference that was proportional to the greater extracellular water content of the slow-twitch fibers. 33 The importance of water compartmentation was substantiated by a higher concentration of infused gadolinium DTPA, a marker of the extracellular space, in slow-twitch fibers. Interestingly, data from one group studying humans reported opposite findings.…”
Section: Muscle Fiber Typingmentioning
confidence: 99%
“…[12] an estimate of K is necessary for the determination of T 2I . Methods in the literature proposed for the measurement of K (21,44) involve studies of longitudinal signal recovery (T 1 ) in the presence of intravascu- lar contrast agents at high fields.…”
Section: Extracting Physical Parameters From Decay Measuresmentioning
confidence: 99%
“…Results in various muscle types with different capillary densities indicated significant (10) or no (11) differences with monoexponential T 2 fits. Fits for multiexponential decay found two (11,12) or three (10,13,14) T 2 components in normal muscle. When three T 2 components were fit, the shortest T 2 component was approximately 5 msec.…”
mentioning
confidence: 92%
“…Their results indicate that both the short and long T2 components of fast-and slow-twitch muscle are similar under normal conditions. Adzamli et al (16,17) have made both T1 and T2 measurements of rabbit fastand slow-twitch fibers immediately following excision at 10 MHz. They have fitted single component models using log-linear least squares regression and multicomponent models using a maximum likelihood algorithm based on Poisson statistics ( 18).…”
Section: Introductionmentioning
confidence: 98%